Biomanufacturing by in vitro biosystems containing complex enzyme mixtures. (January 2017) - You, Chun; Percival Zhang, Y.-H.
Highlights: In vitro biosystems can be the comparable platform with microbial fermentation. The advantages of in vitro biosystems are illustrated by several examples. Product cost of in vitro biosystems is mainly determined by enzyme and coenzyme cost. The challenges of in vitro biosystems for industrial biomanufacturing are introduced. The design principles of in vitro biosystems for manufacturing are discussed. Abstract: Microbial fermentation is the current predominant biomanufacturing platform. However, it suffers from low production yields, slow reaction rates, and scaling-up challenges. In vitro enzymatic biosystems are emerging to expand the traditional biotechnological mode by utilizing more than three enzymes for manufacturing the desired product from cheap substrate. In the past few years, numerous proofs of the concept of in vitro biosystems containing complex enzyme mixtures from different groups worldwide have inspired the development of these platforms for biomanufacturing, these biosystems show advantages such as near-theoretical product yields, faster reaction rates, reduced interference from toxic compounds, and unprecedented level of engineering. In this review, several examples of in vitro systems are presented to illustrate these advantages and possible solutions to overcome the remaining challenges are discussed. The continuing decrease in enzyme cost and improvements in enzyme engineering techniques will make in vitro biosystems a comparable biomanufacturing platform for microbial fermentation in the near future.